![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: (a-b)x2+(b-c)x+(c-a)=0 - if the roots of the equation (a-b)x2+(b-c)x+(c-a)=0 are equal then prove that 2a=b+c - if the roots of the equation (b-c)x2+(c-a)x+(a-b)=0 are equal then prove that 2b=a+c - (a b)x2+(b c)x+(c a)=0 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.